Analisis Digitalisasi Perpajakan Dalam Meningkatkan Kepatuhan Wajib Pajak; Systematic Literature Review - Sitio, Maha Pradana; Hendarto, Deny Tri; Hudi, Norman Alam; Sunarsih, Uun; Mais, Rimi Gusliana (Syntax Literate, 2025)
Digital transformation in the tax system is a strategic step by the government to improve taxpayer compliance. This study aims to analyze the effect of tax digitalization on improving taxpayer compliance through the Systematic Literature Review (SLR) approach. The study was conducted on 13 scientific articles published in the period 2023–2025, data obtained from the garuda.kemdikbud.go.id database and using the Charting the Field approach. The results of the study indicate that tax digitalization has a positive effect on improving taxpayer compliance. The main factors influencing taxpayer compliance are the level of digital literacy, the reliability of information technology infrastructure, and socialization and assistance provided by the Directorate General of Taxes (D). This study provides a theoretical contribution by strengthening understanding based on the Theory of Planned Behavior and Self Assessment System in tax compliance, and offers practical implications for policy makers to develop a more inclusive, responsive, and sustainable tax system in the era of digital transformation.